PEDULI COVID-19 BAGI ANAK-ANAK OTG (ORANG TANPA GEJALA) DI TEMPAT KARANTINA DUTA COVID-19 ALMADERA HOTEL - Andi Meinar Dwi Rantisari; Sulfiani Sulfiani (Gapenas Publisher, 2021)
During the COVID-19 outbreak, a social phenomenon emerged that could potentially exacerbate the situation: the emergence of social stigma and discrimination against COVID-19 patients, not to mention children with OTG status in quarantine. This situation can trigger anxiety and stress, which can have an impact on their immunity. In addition, children with OTG status in the quarantine may be vulnerable to stress because environmental changes and activity restrictions can make children easily psychologically depressed. The purpose of this Activity is to provide donations to OTG children at the Covid 19 Ambassador Quarantine at the Almadera Makassar Hotel and as a form of support for the government in tackling the COVID 19 pandemic in Indonesia, especially in the city of Makassar, South Sulawesi. The steps taken in this Activity began with Opening, Providing donations in storybooks, toys, and milk, and Distract Activity which involved the COVID 19 Ambassador Task Force Team of the South Sulawesi Provincial Health Office and lecturers at Megarezky University. Based on the results of the implementation of the community service program that this Activity went well and smoothly. This is known from the level of attendance and Activity of the participants. The total participants were 19 people, OTG children, and volunteers from the COVID 19 Task Force who served at the Almadera Hotel. The participants who attended were very enthusiastic. The result of this Activity is that it is hoped that it can increase awareness of the survivors of COVID 19 so that they can increase their enthusiasm and immunity so that they recover quickly and return home